PREDICTION OF INDUSTRIAL ENTERPRISES DEVELOPMENT ON THE BASIS OF NEURONETS CONSTRUCTION (BY EXAMPLE OF ASTRAKHAN REGION) - N. Sh. Epifanova (Russian Journal of Economics and Law, 2012)
The article grounds the use of neuronets predicting as a tool for determining the main trends of development of the industrial enterprises of a region. The neuronets architecture is constructed, which is the basis for predicting the main medium-term indicator of industrial enterprises' efficiency (production index) by all kinds of economic activity, and their estimation is presented.